Cortical plasticity as a basis of phantom limb pain: fact or fiction? - Andoh, Jamila; Flor, Herta (Neuroscience, 2017)
Cortical reorganization has been proposed as a major factor involved in phantom pain with prior nociceptive input to the deafferented region and input from the non-deafferented cortex creating neuronal activity that is perceived as phantom pain. There is substantial evidence that these processes play a role in neuropathic pain, although causal evidence is lacking. Recently it has been suggested that a maintenance of the cortical representation of the former hand area is related to phantom pain. Although interesting, evidence for this process is so far scarce. In addition, peripheral factors have been proposed as important for phantom limb pain. Although often introduced as contradictory, we suggest that cortical reorganization, preserved limb function and peripheral factors interact to create the various painful and nonpainful aspects of the phantom limb experience. In addition, the type of task (sensory versus motor), the interaction of injury- and use-dependent plasticity, the type of data analysis, contextual factors such as the body representation and psychological variables determine the outcome and need to be considered in models of phantom limb pain. Longitudinal studies are needed to determine the formation of the phantom pain experience.